Employers’ perception and expectation of the graduates competency - Daud, Fatimah @ Hasnah (2010)
This research discusses the employers’ perception and expectation of the undergraduate competency and personality. Research methodology is based on questionnaires survey and in depth interview on 100 employers. It focuses on employers that consist private and public sectors. The main findings show that factors such as mediocre or low academic achievement, low English language proficiency, inconsistency in competency and personality characteristics those observed on unemployed graduates and those aspired by employers are the causes of the unemployment among graduates.